1991
DOI: 10.1083/jcb.112.5.1031
|View full text |Cite
|
Sign up to set email alerts
|

The properdin-like type I repeats of human thrombospondin contain a cell attachment site.

Abstract: Abstract. Thrombospondin (TS) is a modular adhesive glycoprotein that contains three domains previously implicated in the attachment of cells to "IS. These include the amino-terminal heparin-binding domain, the carboxy terminal cell or platelet-binding domain, and an RGDA sequence of TS. We have characterized a mAb against human TS, designated A4.1, which inhibits the attachment of human melanoma cells (G361) to TS. The epitope for A4.1 lies within the amino terminal half of the central stalklike region of "IS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
150
1
1

Year Published

1993
1993
1999
1999

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 227 publications
(160 citation statements)
references
References 46 publications
7
150
1
1
Order By: Relevance
“…Further investigation established that TSP was also secreted by a variety of cultured cells that include endothelial cells (McPherson et al, 1981;Mosher et al, 1982;Canfield et al, 1990), smooth muscle cells and fibroblasts (Raugi et al, 1982;Jaffe et al, 1983), keratinocytes (Wikner et al, 1987), macrophages (Jaffe et al, 1985), and glial cells (Asch et al, 1986). These findings, coupled with reports describing several cell-surface receptors for the protein Taraboletti et al, 1987;Lawler et al, 1988;Kaesberg et al, 1989;Frazier, 1991;Prater et al, 1991;Guo et al, 1992;Leung et al, 1992), indicated a broader spectrum of functions than that initially recognized in coagulation.…”
Section: Introductionmentioning
confidence: 94%
“…Further investigation established that TSP was also secreted by a variety of cultured cells that include endothelial cells (McPherson et al, 1981;Mosher et al, 1982;Canfield et al, 1990), smooth muscle cells and fibroblasts (Raugi et al, 1982;Jaffe et al, 1983), keratinocytes (Wikner et al, 1987), macrophages (Jaffe et al, 1985), and glial cells (Asch et al, 1986). These findings, coupled with reports describing several cell-surface receptors for the protein Taraboletti et al, 1987;Lawler et al, 1988;Kaesberg et al, 1989;Frazier, 1991;Prater et al, 1991;Guo et al, 1992;Leung et al, 1992), indicated a broader spectrum of functions than that initially recognized in coagulation.…”
Section: Introductionmentioning
confidence: 94%
“…Recombinant fragments and GST or T7 fusion proteins expressing fragments of TSP1 were prepared as described (15,19,20). Synthetic peptides containing TSP1 sequences were prepared as described previously (2,14,(21)(22)(23)(24). Bovine type I collagen was obtained from Collaborative Research, and human vitronectin was from Sigma.…”
Section: Methodsmentioning
confidence: 99%
“…The Mal II peptide promotes adhesion of these cells (23), but it does not activate ␣ v ␤ 3 integrin. Direct adhesion to peptides 246 and 7N3 in the absence of an ␣ v ␤ 3 integrin ligand induces a signal that opposes that induced by the same peptide when added in solution.…”
Section: Enhancement Of Melanoma Cell Spreading By Soluble Tsp1mentioning
confidence: 99%
“…After a 30-rain incubation at 37~ the nonadherent cells were washed offwith 3 rounds of gentle pipetting. The residual adherent cells were checked by visual inspection, and quantified with a colorimetric reaction using endogenous cellular acid phosphatase activity (52). Optical densities were determined using an ELISA plate reader (Molecular Devices Corp., Menlo Park, CA) with a 410-nM filter.…”
Section: Assays Of Cell Adhesion To Immobilized Fibronectinmentioning
confidence: 99%